Necrotic loxoscelism in lower limb and reconstruction with skin autograft - Mauricio, Leonel Iturbide; Lopez-Herrera, Hugo E.; Perez-Puertos, Josue I.; Rodriguez-Barrón, Giovanni A.; Guerrero-Mercado, Abigail (International Journal of Research in Medical Sciences, 2024)
Loxesceles are small spiders, from 9 to 25 mm, with a dark brown spot on the dorsal part in the shape of an inverted violin. They are common in northwestern Mexico and can live at temperatures of 8 to 40°C. These spiders are considered of medical importance because their venom is dermonecrotic, with proteolytic and necrotic action, which is generated in two apocrine glands. The cutaneous clinical picture is the most frequent, with edema, erythema and ischemia that tends to evolve to ulceration and deep necrosis. The key to treatment is early debridement to avoid complications. We presented the case of a 57-year-old female patient who developed an inflammatory condition secondary to a fiddler spider bite involving the left lower extremity. Her evolution to necrosis and late diagnosis required surgical debridement and use of negative pressure therapy (VAC), followed by harvesting and placement of partial thickness skin autograft, obtaining a successful aesthetic and functional result.